1985
DOI: 10.1007/bf01997967
|View full text |Cite
|
Sign up to set email alerts
|

Damage components of powdery mildew in winter wheat

Abstract: The photosynthesis and transpiration rates of winter wheat leaves were measured at different developmental stages and at various levels of mildew infection. Even at low levels of infection, circa 40Jo leaf area being covered, both the assimilation and transpiration rates at light satiation were considerably reduced. Light use efficiency and dark respiration were not significantly affected. The physiological background of these effects was analysed by photosynthesis measurements at different external COz concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2
9

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 10 publications
3
31
2
9
Order By: Relevance
“…The rust accelerated foliage senescence, reducing the cumulative light interception of the crop and so its total dry matter production, which was proportional to the light interception. The applicability of such a crop physiological analysis to disease or pest-induced yield losses was also demonstrated by, among others, Rossing et al (1989), Waggoner and Berger (1987), Johnson (1987), Van Roermund et al (1986), Rabbinge et al (1985). The results of photosynthesis measurements in the field support the hypothesis that leaf rust in winter wheat reduces crop photosynthesis by reducing the green, photosynthesizing area without affecting the photosynthetic rate per unit of remaining green surface.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The rust accelerated foliage senescence, reducing the cumulative light interception of the crop and so its total dry matter production, which was proportional to the light interception. The applicability of such a crop physiological analysis to disease or pest-induced yield losses was also demonstrated by, among others, Rossing et al (1989), Waggoner and Berger (1987), Johnson (1987), Van Roermund et al (1986), Rabbinge et al (1985). The results of photosynthesis measurements in the field support the hypothesis that leaf rust in winter wheat reduces crop photosynthesis by reducing the green, photosynthesizing area without affecting the photosynthetic rate per unit of remaining green surface.…”
Section: Discussionmentioning
confidence: 91%
“…96 (1990) estimate of the reduction in photosynthetic capacity of the foliage. The situation may be different for other diseases, as suggested, for instance, by the results of Rabbinge et al (1985) who found that a 40Jo coverage of powdery mildew in wheat reduced leaf photosynthesis by 50%.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, em outros, a taxa fotossintética é reduzida também no tecido verde, aparentemente sadio, ao redor das lesões (Rabbinge et al, 1985;Bastiaans, 1991;Goodwin, 1992;Shtienberg, 1992;Bassanezi et al, 1997). Para determinar o tipo de efeito causado pelo patógeno, Bastiaans (1991) estabeleceu a função matemática P x /P o =(1-x) β que relaciona severidade da doença (x) e taxa fotossintética líquida relativa da folha (P x /P o ), onde P x é a fotossíntese líquida da folha com severidade de doença x e P o é a fotossíntese líquida média de folhas sadias.…”
Section: Abstract Changes In Photosynthesis and Transpiration Of Cornunclassified
“…Esse mesmo efeito já foi constatado para patossistemas como Erysiphe graminis -trigo [Triticum aestivum (L.) Thell.] (Rabbinge et al, 1985;Shtienberg, 1992), Magnaporthe grisea (Hebert) Yaegashi & Udagawa -arroz (Bastiaans, 1991) (Shtienberg, 1992), Xanthomonas campestris pv. phaseoli (Smith) Dye -feijoeiro (Phaseolus vulgaris L.) (Goodwin, 1992) e o fato dos ensaios terem sido realizados no campo.…”
Section: Abstract Changes In Photosynthesis and Transpiration Of Cornunclassified
“…Models of crop growth, which compute yield from temperature and radiation, provide another option to answer the question if they can be combined with models of the pathogen. Rabbinge et al (1985) quantified the effect of powdery mildew on photosynthesis of wheat leaves (Allen, 1942;Walters and Ayres, 1984). How these effects on photosynthesis measured in the laboratory may be used to estimate loss of kernel yield and to what extend they explain yield loss caused by mildew in the field remained to be answered.…”
Section: Introductionmentioning
confidence: 99%